Analytical direct planetary perturbations on the orbital motion of satellites - Frouard, Julien [UNESP]; Yokoyama, Tadashi [UNESP] (Springer Nature, 2013)
An analytical expansion of the disturbing function arising from direct planetary perturbations on the motion of satellites is derived. As a Fourier series, it allows the investigation of the secular effects of these direct perturbations, as well as of every argument present in the perturbation. In particular, we construct an analytical model describing the evection resonance between the longitude of pericenter of the satellite orbit and the longitude of a planet, and study briefly its dynamic. The expansion developed in this paper is valid in the case of planar and circular planetary orbits, but not limited in eccentricity or inclination of the satellite orbit. © 2012 Springer Science+Business Media Dordrecht.
Keywords: Analytical expansion; Evection; Planetary perturbations; Satellite dynamics; Secular motion